Proposição de um indicador para aferir gentrificação - Barros, Ana Carolina dos Santos (2023)
This research was based on information modeling and the use of urban metrics, in the city of Fortaleza, Ceará, Brasil. It has as a starting point the implementation of a Health Innovation District - DIS, in the municipality. Urban planning often follows a marketing logic that, embedded in itself, entails the admission of exclusionary processes. For some authors, for example, there is no doubt that the way urban land is used and the way urban land use instruments are managed is influenced by political and economic forces, mainly related to the real estate market, which is largely responsible for the factual development of cities. Others even speak of disinvestment and precarity politically planned for future market gains, showing the close links between politics, the market and private interests. In this context, the concept of gentrification - understood as a socio-economic process of exclusion - refers to changes suffered by degraded areas that begin to attract higher-income residents, which in turn leads to economic upgrading and increased demand for specialized services in the area, culminating in the displacement of the original residents, who are usually associated with a higher degree of vulnerability and can no longer afford the high new cost of living in this new situation. Based on the insight that it is necessary to understand a phenomenon in order to then be able to address it, the present work aims to present the construction of a system of indicators - understood as a methodological tool to objectify the operationalization of an abstract concept - that can propose a method to measure the propensity of a given area to undergo gentrification processes in the defined spatial section. The hypothesis presented is that information modeling, as a support to urban planning, can help develop tools to describe and predict the occurrence of gentrification and thus contribute to its mitigation. For the methodological construction of the proposed indicator system, after examining case studies and reviewing the literature, we set out to determine the operational dimensions that apply to a possible indicator of gentrification in the community. The summary of previous experiences and the preview of urban variables related to the process, once contextualized and properly applied to our near reality, will guide the proposal for the indicator system - the main product of this research - an analysis of descriptive character in the defined spatial section. Therefore, it is expected to improve the visibility of processes and exclusion dynamics related to gentrification in the city of